การติดตามวัตถุที่เคลื่อนที่โดยใช้หุ่นยนต์พิกัดฉาก 3 แกนอาศัยการขับเคลื่อนเชิงภาพ - พรพิศุทธิ์ โลหิตหาญ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This research focuses on the real-time target tracking for a Cartesian robot in 2 dimensions by using visual servo control. It is the process of controlling a system in servo-loop by using visual image data as a referenced command to control the motion of a robot. The visual servo control can be divided into 2 loops. The first loop is image processing loop for tracking a target in video frame and the second loop is servo loop for feedback control of a Cartesian robot. A target tracking is based on color probability image using The CAMShift (Continuously Adaptive Mean Shift) algorithm to find the most possible target position from color histogram in the current frame with a single camera fixed in a reference frame. The experimental results illustrate that a Cartesian robot is automatically track and record the positions of a moving target or fixed target. The performance of this visual servo control can be adapted to more complex control applications.